2019
DOI: 10.1371/journal.pone.0222267
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selective cytotoxicity of the dietary chalcone cardamonin (CD) on melanoma compared to healthy cells is mediated by apoptosis

Abstract: Malignant melanoma is an aggressive type of cancer and the deadliest form of skin cancer. Even though enormous efforts have been undertaken, in particular the treatment options against the metastasizing form are challenging and the prognosis is generally poor. A novel therapeutical approach is the application of secondary plant constituents occurring in food and food products. Herein, the effect of the dietary chalcone cardamonin, inter alia found in Alpinia species, was tested using human malignant melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 96 publications
(132 reference statements)
1
14
0
Order By: Relevance
“…However, it is known that the number of hydroxyl groups and their positioning can regulate the ability of chalcones to uncouple the mitochondria by collapsing the mitochondrial membrane [38], suggesting that structural differences between chalcones may account for the differences in the magnitude of their cytotoxic effects on NB cells. Another chalcone, cardamonin, has been found to selectively induce death of human melanoma cells, and not on healthy human melanocytes or dermal fibroblasts [57]. This is consistent with the selectivity cytotoxicity of low doses of 4HC on MYCN -amplified NB but not on cultured midbrain neurons, found here in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is known that the number of hydroxyl groups and their positioning can regulate the ability of chalcones to uncouple the mitochondria by collapsing the mitochondrial membrane [38], suggesting that structural differences between chalcones may account for the differences in the magnitude of their cytotoxic effects on NB cells. Another chalcone, cardamonin, has been found to selectively induce death of human melanoma cells, and not on healthy human melanocytes or dermal fibroblasts [57]. This is consistent with the selectivity cytotoxicity of low doses of 4HC on MYCN -amplified NB but not on cultured midbrain neurons, found here in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the DCM extract was located close to MCF-7. This extract contains several compounds at medium polarity with a major compound: cardamon is known according to the literature by its cytotoxic properties [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2019) In vivo H460 xenograft ↓Tumor growth, Ki-67, PI3K/Akt/mTOR Zhou et al. (2019) In vitro A549 ↓Cell migration, G2/M phase arrest, ↑apoptosis, ↑caspase-3/7, ↑caspase-9, ↑PARP cleavage, ↓Mcl-1, ↓p-mTOR, ↓p-4EBP1 C Break et al, (2018) Melanoma In vitro A375 ↓Cell viability, invasion, ↑apoptosis, caspase-3, ↑PARP Berning et al. (2019) Myeloma In vitro RPMI 8226, U266, ARH-77, RPMI 8226 ↓Cell proliferation ↑ Apoptosis, caspase-3, PARP, ↓Bcl-2, Bcl-xL, ↓ survivin, XIAP, cIAP-1, cIAP-2, NF-κB/p65, ↓IKK, IKKβ, p-IκBα, ICAM-1, COX-2, VEGF Qin et al (2012) NPC In vitro HK1 ↓Cell migration, G2/M phase arrest, ↑apoptosis, ↑caspase-3/7, ↑caspase-9, ↑PARP cleavage, ↓Mcl-1, ↓p-mTOR, ↓p-4EBP1 C Break et al., (2018) Ovarian Cancer In vitro SKOV3 ↓Cell viability, VEGF, HIF-1α, HIF-2α, ↓p-mTOR, p-S6K1 Xue et al, (2016) In vitro SKOV3 ↓p-Raptor, mTORC1, p-S6K1, Lamp2 Shi et al.…”
Section: Biological Activities Of CDmentioning
confidence: 99%
“…In addition, the treatment of CD was shown to induce apoptosis, suppress cell proliferation, invasion, etc. in human malignant carcinoma cell lines ( Berning et al., 2019 ). These studies indicated the possible use of CD as a therapeutic agent against melanoma ( Shannan et al., 2016 ).…”
Section: Biological Activities Of CDmentioning
confidence: 99%